Steatotic Liver Disease Education Enhances Knowledge and Confidence to Adhere to Provider Recommendations in Diverse and Vulnerable Populations - Shyam Patel; Diana Partida; Catherine Magee; Flor E. Garza Romero; Jennifer Y. Chen; Michelle Tana; Mandana Khalili (Gastro Hep Advances)
Background and Aims: Patient knowledge of steatotic liver disease (SLD) is suboptimal. We assessed the impact of SLD education on patient knowledge and confidence to follow provider recommendations among a diverse vulnerable population. Methods: In this prospective study from February 19, 2020, to January 31, 2024, 296 adults with SLD were surveyed before and after receipt of formal SLD education. Linear regression (adjusted for age, sex, race) assessed factors associated with baseline SLD knowledge score and its change after education (delta in prescores and postscores), along with confidence to follow provider recommendations following receipt of education. Results: Participant characteristics were as follows: median age 53 years, 40.9% male, 55.1% Hispanic (27.0% Asian and 10.5% White), and 23.8% reported heavy alcohol use. SLD knowledge and confidence to follow provider recommendations increased posteducation (all P < .05). On multivariable analyses, greater than high school education (vs high school or less) (coef. 0.62), perceived severity of disease (coef. 0.62), treatment efficacy (coef. 1.38), self-efficacy to discuss SLD (coef. 0.71), and perceived susceptibility to disease risk (coef. 0.93) were associated with greater baseline knowledge (all P < .05). Following education, heavy alcohol use (vs none) was associated with greater change in knowledge (coef. 0.74), while perceived severity (coef. −0.52) and treatment efficacy (coef. −0.72) were associated with lesser change in knowledge (all P < .05). While perceived barriers (coef. −0.14) were associated with less confidence, self-efficacy to discuss SLD, older age, Hispanic, and other race was associated with greater confidence to follow provider recommendations (coef. 0.38, 0.18, 0.64, and 1.26, respectively, all P < .05). Conclusion: Formal SLD education enhanced knowledge and confidence to follow provider recommendations in Hispanics and heavy alcohol users. SLD education is integral to SLD management in safety net populations.